TOTAL NITROGEN DETERMINATION IN AMMONIACAL, AMIDIC AND NITRATE NITROGEN CONTAINING FERTILIZERS BY THE RANEY CATALYST METHOD - Nogueira, Raquel; Santos Neto, Orlando; LourenÃ§o, Rafael Martins; Sena, Claudia Oliveira; Silva, Carlos Magno Wonghan da (REVISTA DE AGRICULTURA, 2022)
This paper presents the optimized conditions for the determination of total nitrogen in ammoniacal, amidic, and nitrate nitrogen containing fertilizers by the Raney catalyst method using a Buchi K-436 speed digester and a Buchi K-360 distillation unit.